Peningkatan Nilai Tambah Produk Aren melalui Diversifikasi Gula Batok menjadi Gula Semut berbasis Teknologi Tepat Guna di Desa Giri Madia, Kecamatan Lingsar, Kabupaten Lombok Barat - Aisah Dwi Lestari; Ida Ayu Widhiantari; Dygta Tri Juandti; Muh. Fajar Islam; M. Hairul Azmi; M. Khairul Hasbi; M. Khairul Rizal; Sakinah; Salma; Tiara Kurnia Sari Dewi (Jurnal Pengabdian Magister Pendidikan IPA, 2026)
Arenga sap is the primary raw material utilized by the community of Giri Madia Village, predominantly processed into conventional palm sugar blocks. However, the quality of the produced sugar remains low due to traditional processing methods, resulting in a relatively short shelf life and limited market value. Additionally, the lack of knowledge regarding product diversification has prevented the community from optimizing the potential of derivative products such as palm sugar granules (gula semut). Through the KKN-T program, an initial observation was conducted to identify issues found in the village’s production process, followed by a technical trial of granulated palm sugar processing using a crystallization machine, a drying oven, and a grinding machine. The results demonstrated that the application of appropriate technology significantly improves product quality, particularly in terms of texture, moisture content, and product stability. A socialization session was conducted to inform the community that palm sugar blocks can be converted into granulated palm sugar through reheating, crystallization, and drying processes. The introduction of this technology enhanced the community’s understanding of product diversification and broader market opportunities. Positive responses from participants indicated that the activity effectively addressed previously encountered issues and increased motivation among artisans to develop higher-value palm sugar products. Thus, the socialization and demonstration activities serve as an initial step toward enabling the Giri Madia community to optimize palm-based products as a competitive and sustainable local commodity.